More on iSchools - Pérez-Agí¼era, José R. (Anuario ThinkEPI, 2010)
The author reflects on the iSchools movement and the need to increase the study of computing in LIS courses. He argues that libraries and archives are only a tiny portion of the places information professionals might work, although library topics occupy almost the entire content of the coursework. The iSchools concept applied in the School of Library and Information Science, University of North Carolina at Chapel Hill, is analysed. The iSchools try to integrate the concept of information from the theoretical point of view, given that information can be defined in many different ways because it is a complex reality that can be analyzed simultaneously from different points of view.